1992
DOI: 10.1055/s-2007-1003274
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Vasopressin Infusion Increases Plasma Levels of Atrial Natriuretic Factor in Humans

Abstract: Seven normal subjects underwent sequential 20-min infusion of arginine vasopressin (AVP) at 0.5 and 2 ng/(kg.min) and a complete right-side heart hemodynamic evaluation during the study to analyze the effect of this hormone on atrial natriuretic factor (ANF) secretion in humans and to elucidate whether this effect was primary or secondary to the hemodynamic or hormonal changes induced by AVP. Plasma ANF levels increased at the end of the first (P less than 0.05) and second (P less than 0.01) infusion periods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The possible candidate for the interaction would be norepinephrine (4), as in the case of PGE2. However, whether AVP would release catecholamines from the sympathetic nerve endings has been controversial (17), and therefore the interaction with catecholamines does not definitely seem, at least now, to be a possible explanation for the action of AVP on FBM and LVF activity. Another candidate with which AVP inhibits FBM is ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…The possible candidate for the interaction would be norepinephrine (4), as in the case of PGE2. However, whether AVP would release catecholamines from the sympathetic nerve endings has been controversial (17), and therefore the interaction with catecholamines does not definitely seem, at least now, to be a possible explanation for the action of AVP on FBM and LVF activity. Another candidate with which AVP inhibits FBM is ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ANP reportedly inhibits the secretion (Samson, 1985) and action (Dillingham & Anderson, 1986) of vasopressin, though in an in vitro study synthetic atrial natriuretic peptide induced release of arginine vasopressin from the isolated posterior lobe of the rat hypophysis (Januszewicz, Gutkowska, De Lean, Thibault, Garcia, Genest & Cantin, 1985). It has been shown that AVP Sanz, Revert & Rivera-Fillat, 1992) and in anaesthetized rats stimulates the release of ANP (Manning, Schwartz, Katsube, Holmberg & Needleman, 1985). Morris, Cain & Chalmers (1987) have also reported that reciprocal changes in plasma ANP and AVP concentrations occur in response to volume expansion and haemorrhage in conscious stroke-prone spontaneously hypertensive rats, spontaneously hypertensive rats and normotensive Wistar-Kyoto rats.…”
Section: Introductionmentioning
confidence: 99%